Comparison of treatment effect of neuromuscular electrical stimulation and thermal-tactile stimulation on patients with sub-acute dysphagia caused by stroke - Koh, Hyeung Woo; Byeon, Haewon (Journal of Physical Therapy Science, 2016)
[Purpose] The effectiveness of neuromuscular electrical stimulation in the rehabilitation of swallowing remains controversial. This study compared the effectiveness of neuromuscular electrical stimulation and thermal tactile oral stimulation, a traditional swallowing recovery treatment, in patients with sub-acute dysphagia caused by stroke. [Subjects and Methods] Subjects of the present study were 55 patients diagnosed with dysphagia caused by stroke. This study had a nonequivalent control group pretest-posttest design. [Results] Analysis of pre-post values of videofluoroscopic studies of the neuromuscular electrical stimulation and thermal tactile oral stimulation groups using a paired t-test showed no significant difference between the two groups despite both having decreased mean values of the videofluoroscopic studies after treatment. [Conclusion] This study’s findings show that both neuromuscular electrical stimulation and thermal tactile oral stimulation significantly enhanced the swallowing function of patients with sub-acute dysphagia.